1991
DOI: 10.1016/s0022-5347(17)38467-7
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma of the Spermatic Cord

Abstract: Malignant tumors of the spermatic cord are rare but the vast majority of these tumors are sarcomas. We report on a patient with osteosarcoma arising in the spermatic cord. Left radical orchiectomy with high dissection of the spermatic cord was performed, and the patient remains free of recurrence 2 years postoperatively. We could find no previous discussion or report of this tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Local relapse is a significant problem following orchiectomy, and reports have suggested that additional local treatment with surgery or irradiation may improve local control (11). In the case of osteosarcoma of paratesticular spermatic cord, complete excision of the tumor with radical inguinal orchiectomy and high ligation of the spermatic cord was the main primary surgical procedure (1,2,12). A more aggressive surgical policy in the management of spermatic cord sarcomas has been proposed as primary surgery, involving wide excision of surrounding soft tissue and re-excision in the case of local recurrence of the disease, since of the patients without clinically apparent disease who underwent re-excision, residual tumor was discovered in almost one third of the cases (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local relapse is a significant problem following orchiectomy, and reports have suggested that additional local treatment with surgery or irradiation may improve local control (11). In the case of osteosarcoma of paratesticular spermatic cord, complete excision of the tumor with radical inguinal orchiectomy and high ligation of the spermatic cord was the main primary surgical procedure (1,2,12). A more aggressive surgical policy in the management of spermatic cord sarcomas has been proposed as primary surgery, involving wide excision of surrounding soft tissue and re-excision in the case of local recurrence of the disease, since of the patients without clinically apparent disease who underwent re-excision, residual tumor was discovered in almost one third of the cases (13).…”
Section: Discussionmentioning
confidence: 99%
“…Primary osteosarcoma of paratesticular soft tissue is a rare tumor, with few reports in the literature (1)(2)(3). To the best of our knowledge, only one case (4) arising directly from paratesticular soft tissue has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A few reports of paratesticular fibrosarcomas [10,12] and malignant fibrous histiocytomas [12] are present in the literature. To the best of our knowledge, only two reports of primary osteosarcomas of the spermatic cord are described in the literature [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Primary extraskeletal osteosarcomas of the genitourinary tract are rare. Very few case reports describing primary osteosarcoma of the spermatic cord are to be found in the literature [4,5]. We report a case of primary paratesticular osteosarcoma in which the patient died 6 months after the diagnosis.…”
Section: Introductionmentioning
confidence: 91%
“…There are very few reported cases of primary extraskeletal osteosarcoma of the spermatic cord ( 77 - 79 ). Patients present with a painless mass that is generally calcified on a CT scan ( 77 , 78 ).…”
Section: Malignant Neoplasmsmentioning
confidence: 99%